2013
DOI: 10.1007/s10800-012-0523-0
|View full text |Cite
|
Sign up to set email alerts
|

Activity and active sites of nitrogen-doped carbon nanotubes for oxygen reduction reaction

Abstract: Nitrogen-doped carbon (CNx) nanotubes were synthesized by thermal decomposition of ferrocene/ethylenediamine mixture at 600-900°C. The effect of the temperature on the growth and structure of CNx nanotubes was studied by transmission electron microscopy, X-ray photoelectron spectroscopy, and Raman spectroscopy. With increasing growth temperature, the total nitrogen content of CNx nanotubes was decreased from 8.93 to 6.01 at.%. The N configurations were changed from pyrrolic-N to quaternary-N when increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 37 publications
(65 reference statements)
1
24
0
Order By: Relevance
“…Pyrolysis of alkylamines was also frequently employed synthetic route to NCNTs, mainly MWNCNTs (Table 3) [101,[131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146]. A novel simple approach, quite different from classic CVD processes, has recently been developed for synthesizing NCNTs from flames using liquid alkylamines as fuels, which created a high reaction temperature and provided a C/N source [132].…”
Section: Arc-discharge and Laser Ablationmentioning
confidence: 99%
“…Pyrolysis of alkylamines was also frequently employed synthetic route to NCNTs, mainly MWNCNTs (Table 3) [101,[131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146]. A novel simple approach, quite different from classic CVD processes, has recently been developed for synthesizing NCNTs from flames using liquid alkylamines as fuels, which created a high reaction temperature and provided a C/N source [132].…”
Section: Arc-discharge and Laser Ablationmentioning
confidence: 99%
“…Based on previous research reports, the opinion was supported on the ORR activity of N-doped carbon, various nitrogen configurations are not all active sites for ORR. Furthermore, among the active sites, quaternary-N may be stable active sites while pyridinic-N is not that much stable for the acid condition as in the ORR [33].…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the ILC-900 °C showed the highest ORR activity with a best onset potential and diffusion-limited current. This result came from the physical and electrochemical characterizations that suggest the total nitrogen amount and all nitrogen configurations are not the active sites for ORR, though quaternary nitrogen may be the active sites for the increase in electrochemical activity and conductivity by the graphitic structure [33]. It can be concluded that the ORR activity is 6 shows the catalytic activities of the prepared catalysts in oxygen saturated 0.5 M H 2 SO 4 solution at room temperature using a potential scan rate of 5 mV/s and a rotation rate of 1600 rpm.…”
Section: Resultsmentioning
confidence: 99%
“…Qiu 27 treated carbon nanotubes (undoped) with ammonia, and found that ORR starts at 0.72 V/SHE. Furthermore, Dorjgotov 28 synthesized N-CNT from ethylenediamine at different temperatures (600-900…”
Section: Synthesized N-cnts At Different Temperatures (750-950mentioning
confidence: 99%
“…The effect of temperature on the catalytic activity of the N-CNTs under acidic conditions (0.5 M H 2 SO 4 ) has been reported. 25,26,28 Dorjgotov 28 evaluated the catalytic activity of N-CNTs and show the synthesis temperature (600-900…”
Section: Synthesized N-cnts At Different Temperatures (750-950mentioning
confidence: 99%